Design of Digital IFE and EFE Evaluation of A3N 766HI Organic Fertilizer Products to Make Strategic and Sustainable Decisions - Silalahi, Amin (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: to answer the question, "Will the digital evaluation design for IFE and EFE of the A3N 766HI organic fertilizer product facilitate the strategic and sustainable decision-making process by using the SPSS and smart PLS’ tools?" Design/Methode/Approach: using the mixed method, namely a qualitative and quantitative method in the form of a case study. Research Finding: The results from the IFE and EFE digital evaluation designs greatly facilitate strategic and sustainable decision-making, where the IFE value is 3.25 and the EFE value is 3.20 with a weight value of 1.00, designed to be a digital value. Theoretical contribution/originality: The business environment can influence important variables such as strategic planning, business performance, competitive advantage, strategy innovation, technology strategy, and corporate sustainability (Dyllick & Hockerts, 2017). Digital strategies can play an essential role in enhancing sustainability performance by enabling organizations to scan their ecological and social impacts more effectively, adopt sustainable business practices, and enhance the efficiency and effectiveness of business processes. Ukko, J.; Nasiri, M.; Saunila, M.; Rentala, T. (2019); and Huong, T.T.I.; Thanh, T.T. Practice/Policy Implications: Helping to make decisions sustainably and develop strategies by using the tools SPSS and Smart PLS to analyze the internal factor evaluation (IFE) and external factor evaluation (EFE). Research limitation: this study is limited to a case study. This response to this study does not yet standardize analysis for internal and external evaluation for the big corporation.